Sagot :
USING THE LAW OF LOGARITHMIC
Answer:
The both sides have a common logarithm, so we can use the equation of the argument of the two logarithms;
- [tex]\boxed{\begin{array}{c}\small{ \tt \red{logx=logy}} \\\small{ \tt \red{x=y}}\end{array}}[/tex]
___________________
[tex]\small{ \tt \green{Solving:}}[/tex]
[tex]\small{ \tt \purple{log(-2x+9)=log(7-4x)}}[/tex]
[tex]\small{ \tt \purple{-2x+9=7-4x}}[/tex]
[tex]\small{ \tt \purple{(4x-9)-2x+9=7-4x+(4x-9)}}[/tex]
[tex]\small{ \tt \purple{2x=-2}}[/tex]
[tex]\small{ \tt \purple{\frac{2x}{2} =\frac{-2}{2} }}[/tex]
[tex]\small{ \tt \purple{x=-1}}[/tex]
___________________
- Therefore, the answer is x = -1.
____________________
#CarryOnLearning